Circulating immune complexes in polymyalgia rheumatica and giant cell arteritis. Issue 4 (August 1981) - Park, J R; Jones, J G; Harkiss, G D; Hazleman, B L
Abstract : Sera from patients with giant cell arteritis and/or polymyalgia rheumatica have been found to contain increased levels of circulating immune complexes (IC). Results with the polyethyleneglycol precipitation complement consumption (PEG-CC) assay have been correlated with disease activity. 44% of samples from an active untreated group (21 patients) had increased levels of ICs compared with 23% from an inactive treated group (49 patients). Further analysis of circulating ICs was performed by 125I-Clq binding, the PEG-C4 test, and 125I-conglutinin binding assays. Although we did not find a high correlation between IC levels and disease activity, isolation and analysis of the ICs may lead to further understanding of this disorder.